1977
DOI: 10.1159/000180782
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hemodialysis and Saline Loading on Body Fluid Compartments, Plasma Renin Activity and Blood Pressure in Patients on Chronic Hemodialysis

Abstract: The influence of one hemodialysis session and of subsequent loading by 1.5–2 liters TV saline on blood pressure, PRA and body fluid compartments was assessed in seven patients with chronic renal failure on maintenance hemodialysis. Dialysis caused only slight decreases in plasma volume, ECV and in TEBS. Lying mean blood pressure decreased by 5–10 mm Hg and PRA increased by 30%. Saline loading resulted in a significant increase in plasma volume by 0.4 liters and in blood pressure by 10–15 mm Hg, but in a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…intradialytic) response of blood pressure to fluid volume changes do not detect this correlation. [10][11][12] But this lack of immediate correlation may well be explained by the large number of clinical experiences indicating a lag time of several days or weeks between a volume change and a succeeding blood pressure change, as referred by Charra. 13 Antihypertensive medications today are very effective in lowering blood pressures, especially in case of normal volume state.…”
Section: Background Relevance Of Fluid Status Normalizationmentioning
confidence: 99%
“…intradialytic) response of blood pressure to fluid volume changes do not detect this correlation. [10][11][12] But this lack of immediate correlation may well be explained by the large number of clinical experiences indicating a lag time of several days or weeks between a volume change and a succeeding blood pressure change, as referred by Charra. 13 Antihypertensive medications today are very effective in lowering blood pressures, especially in case of normal volume state.…”
Section: Background Relevance Of Fluid Status Normalizationmentioning
confidence: 99%
“…Renin and angiotensin II levels per se are widely variable in dialysis patients and not necessarily related to blood pressure levels [35]. However, circulating levels of renin and angiotensin appear to be inappropriately activated in relation to the volume status and exchangeable sodium levels, at least in a subset of dialysis patients [35,36]. In dialysis patients who responded with an increase in blood pressure to short-term volume loading, the decrease in renin and angiotensin II levels tended to be lower compared to the patients in whom blood pressure did not change [12].…”
Section: Volume Sodium and Pressor Systems In Hemodialysis Patientsmentioning
confidence: 99%
“…In patients with ESRD, it has indeed been observed that circulating levels of renin and angiotensin are inappropriately increased in response to the fluid status of the patient, whereas also the normally reciprocal relation-ship between total exchangeable sodium and the activity of the RAAS was found to be disturbed which may result in an inappropriate increase in systemic vascular resistance [18,29]. Nevertheless, other authors [30] observed a normal response of the RAAS to salt and water loading and removal. Therefore, there appear to be large intraindividual differences in the relation between salt/volume and the activity of the RAAS.…”
Section: The Raas and Hypertension In Chronic Renal Failurementioning
confidence: 99%